2018
DOI: 10.1002/ejoc.201800863
|View full text |Cite
|
Sign up to set email alerts
|

Carbene Transfer and Carbene Insertion Reactions Catalyzed by a Mixed‐Ligand Copper(I) Complex

Abstract: The catalytic activity of the mixed‐ligand copper(I) complex [Cu(PPh3)2(κ2‐O,O"‐lact)] (1) {lact = l‐(+)‐lactate} has been investigated in carbene transfer and carbene insertion reactions. Complex 1 catalytically promoted the diastereoselective cyclopropanation of olefins in the presence of ethyl diazoacetate (EDA), under mild conditions, and with a low catalyst loading (1 mol‐%). In the case of internal alkenes, a trans/cis ratio of up to 93:7 was reached. Moreover, compound 1 easily promoted the insertion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…Finally, one diene was also employed as substrate, 2,5‐dimethyl‐2,4‐hexadiene (DMHD), showing a conversion into the corresponding chrysantemate ethyl esters in high yields (up to 90 %, entry 18). Overall, the yields in cyclopropane products are comparable to those reported for the analogous copper(I)‐lactate species [Cu(PPh 3 ) 2 (κ 2 ‐O,O“‐lact)] ( CuP2L ) [34] . Diastereoselectivities were comparable to previous publications as well: a 25 : 75 to 30 : 70 cis / trans ratio was recorded in the catalytic cyclopropanation of internal olefins, with the exception of α‐methylstyrene which was converted with a lower trans diastereoselectivity (ca.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Finally, one diene was also employed as substrate, 2,5‐dimethyl‐2,4‐hexadiene (DMHD), showing a conversion into the corresponding chrysantemate ethyl esters in high yields (up to 90 %, entry 18). Overall, the yields in cyclopropane products are comparable to those reported for the analogous copper(I)‐lactate species [Cu(PPh 3 ) 2 (κ 2 ‐O,O“‐lact)] ( CuP2L ) [34] . Diastereoselectivities were comparable to previous publications as well: a 25 : 75 to 30 : 70 cis / trans ratio was recorded in the catalytic cyclopropanation of internal olefins, with the exception of α‐methylstyrene which was converted with a lower trans diastereoselectivity (ca.…”
Section: Resultssupporting
confidence: 70%
“…Indeed, addition of ethyl diazoacetate to a solution of the olefin and the catalyst (1 % mol) led under mild conditions to the conversion of the substrate into the corresponding cyclopropane derivatives with high yields (Table 2). Like previous studies, [34] the catalytic runs were performed in dichloromethane, at room temperature. As known, side products deriving from EDA self‐coupling (i. e., diethyl maleate and diethyl fumarate) can also be generated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transition metal-catalyzed carbene transfer from diazo derivatives to olefins is a powerful method to give cyclopropane rings. Iglesias and co-workers prepared two imine-linked polymer–organic frameworks (POFs) and modified them with Cu by postsynthetic metalation . They compared the catalytic activity of both Cu 1+ - and Cu 2+ -based POFs for the cyclopropanation of alkenes and found that the Cu 1+ -modified material had higher activity.…”
Section: Resultsmentioning
confidence: 99%